Revitalisasi Permukiman Tradisional sebagai Kawasan Wisata Budaya di Desa Karyamukti Cianjur – Jawa Barat - Diana Susilowati; Aulia Putri Shanty (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2023)
A traditional settlement is an order that has differences that are influenced by its sacred hierarchy or local customary norms. Over time, traditional settlements have been influenced a lot by modernity and the advancement of information around them. Some traditional settlements can maintain their local wisdom but there are some that are affected and adapt to the needs of their environment. As happened in the traditional settlements in Karyamukti village, Gunung Padang Cianjur hamlet. Currently, the condition of these traditional settlements along the path to the Gunung Padang Megalithic site is experiencing the effects of modernity. The growth of the Megalithic site as one of the tourist destinations, makes the surrounding traditional settlements undergo changes, especially the need to support tourist facilities. This research uses descriptive qualitative methods so that it can collect information, both verbally and visually from the element of settlement in Karyamukti village. Based on this, it is necessary to revitalize the traditional settlements in Gunung Padang Hamlet, Karyamukti Tourism Village, to achieve an improvement in the quality of the residential area and be able to become one of the supporting tourist villages as a cultural tourism area. It can contribute science to the arrangement of traditional settlements in other places that have the same background, namely as tourist villages.